Anchoring in economics: On Frey and Gallus on the aggregation of behavioural anomalies - Peter E. Earl (Economics: The Open-Access, Open-Assessment E-Journal, 2015)
This paper examines the research area identified by Frey and Gallus (Aggregate Effects of Behavioral Anomalies: A New Research Area, 2014) and the relationship between it and the choices that economists make. It supports the Frey and Gallus view that, as a consequence of individuals employing external inputs rather than relying upon their own judgemental capacities, the quality of decision-making may differ at the market and macro levels from what has been observed in laboratory experiments. It seeks to forestall potential moves by rational choice theorists to argue that such processes, imposed by competitive pressures, will swiftly eliminate anomalous behaviour. But it questions Frey and Gallus's use of conventional rational choice theory as the reference point for judging the quality of real-world decisions. It argues that choice is an activity based on evolving sets of habits and rules, rather than based on given preference systems, and that Frey and Gallus's failure to consider alternative reference points is itself a manifestation of anchoring.
Keywords: A10; B00; D70; 330; heuristics and biases; infinite regress; rationality